PENGUJIAN BEBERAPA KLON BAWANG MERAH DATARAN TINGGI ( CLONES TESTING OF SOME HIGHLANDS SHALLOTS) - Putrasamedja, Sartono (Pembangunan Pedesaan, 2010)
The research aimed at gaining the clones adapting and giving high yield. The material tested consisted of nine clones and three varieties, i.e., clone 12, 15, 16, 17, 18, 23, 24, 26, and 27, and Betok, Bauji and Bima Brebes. Randomized block design was used and repeated three times. The research was conducted at Balitsa experimental research orchards with altitude of 1250 m above sea level on Andosol soil types and pH 5.1 to 6.2. The result showed that clone 24 had a good vegetative growth and different clones showed the different adaptation power to the society in Lembang. It was showed by clone 18 having higher dry weight per hectare (6.25 ton) supported by higher dry weight per cluster (26.939 g) and per plot (1.209 kg) and able to form an average of 8 sprout.